2015
DOI: 10.1007/s40473-015-0039-0
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Low-Intensity Transcranial Focused Ultrasound for Clinical Applications

Abstract: The field of therapeutic focused ultrasound neuromodulation has made great advances in the last few years. While no clinical trials of focused ultrasound neuromodulation are yet underway, several human experiments have recently been conducted. There are many potential uses of this new technology, including treatment of numerous psychiatric and neurologic disorders, as well as a brainmapping tool for discoveries in basic science. In this review, we examine recent research data on the use of focused ultrasound i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 32 publications
1
37
0
Order By: Relevance
“…[2,13,24,27] The likely basis are mechanical effects on cell membranes affecting mechanosensitive ion channels and generating membrane pores. Several principles, related to different ultrasound-based techniques, have been proposed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2,13,24,27] The likely basis are mechanical effects on cell membranes affecting mechanosensitive ion channels and generating membrane pores. Several principles, related to different ultrasound-based techniques, have been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…[10] Initial clinical data concerning nontargeted stimulation and a case report are also available. It consists of a mobile single transducer system which avoids long sonication trains, [2,13] and therefore the risks of secondary stimulation maxima or brain heating can be avoided. It consists of a mobile single transducer system which avoids long sonication trains, [2,13] and therefore the risks of secondary stimulation maxima or brain heating can be avoided.…”
Section: Introductionmentioning
confidence: 99%
“…By using ultrasound waves (≥ 20 kHz) to penetrate the skull and target brain tissue in a focused way, low-intensity transcranial focused ultrasound (tFUS) has demonstrated its unprecedented capability in non-invasive neural stimulation [1,2], and unparalleled prospects for translational clinical application [3]. Different from high-intensity focused ultrasound (HIFU) [4], low-intensity tFUS can achieve reversible neural effects while complying with the Food and Drug Administration’s (FDA) [5] safety requirements, thus ensuring safety of human subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Our study revealed that US is able to activate A1 with spatial-peak pulse-average acoustic intensities (ISPPA) 302 as low as 20 mW/cm 2 (~25 kPa for the 0.22 MHz transducer), which are lower than what has been 303 previously published for brain activation (Bystritsky and Korb, 2015;Bystritsky et al, 2011;Tufail et al, 304 2010). However, this US-evoked A1 activity is through a non-direct cochlear fluid pathway rather than 305 direct activation of A1 neurons.…”
mentioning
confidence: 50%